Painting Object Film Concept : Works from the Herbig Collection. - Buren, Daniel; Burton, Scott; Francis, Richard; Heinz, Marianne; Hindlip, Lord; Meyer, James; Spector, Naomi; Szeemann, Harald; Tuchman, Phyllis (New York : Christie's, 1998)
Andre, Carl ; Baselitz, Georg ; Beuys, Joseph ; Broodthaers, Marcel ; Buren, Daniel ; Byars, James Lee ; Darboven, Hanne ; Riverhead (New York) ; Gilbert & George ; Heerich, Erwin ; Huebler, Douglas ; Immendorff, Jörg ; Kawara, On ; de Maria, Walter ; Nauman, Bruce ; Oldenburg, Claes ; Palermo, Blinky ; Panamarenko ; Penck, A.R. ; Polke, Sigmar ; Richter, Gerhard ; Roth, Dieter ; Ryman, Robert ; Tuttle, Richard ; Weiner, Lawrence ; Wewerka, Stefan
biografie
Painting Object Film Concept : Works from the Herbig Collection, Christie's, New York, between 17 February and 1 March 1998
Engels
boek